Paciente de sexo femenino de 68 años diagnosticada con nódulo tiroideo hace un año - León Michilena, Sandy Geomara (2020)
In the following clinical case, it is based on a 68-year-old female patient, a native of Jujan, with a diagnosis of Thyroid Nodules since a year ago. On physical examination, it shows blood pressure: 120 / 80mmHg, heart rate: 80 beats / min, respiratory rate: 19 breaths / min, pulse: 85 beats / min, temperature: 37 ° C. In its Biochemical tests, it reflects total cholesterol 211 mg / dl, related to an inadequate diet, high in saturated fats, giving hypercholesterolemia diagnosis considering that it does not present any symptoms since this is a condition that is associated with degenerative development such as it is obesity, which affects the patient's health by decreasing the time and quality of life. It is important to mention that the thyroid stimulating hormone (TSH) was also high (5 mIU / L), indicating a dysfunction of the thyroid gland. A dietary-therapeutic plan of 1705.46 kcal / day divided into four meal times was applied, which improved the nutritional status in 3 months of treatment, where total cholesterol decreased to 178mg / dl (adequate). Thyroid hormone (TSH) improved to 2.2mUI / l (normal).